The Application of Model Thematic Learning to Building Basic Capability for Children with Special Needs - Fadhila Rachmadani; Siti Murtiningsih; Septiana Dwiputri Maharani (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2020)
This research aims to explore the application of thematic learning model and finding its implications to building basic capability for students with special needs. This descriptive research used a qualitative approach and the data collection technique in this research applied purposive sampling. This research on the first stage conducts a descriptive analysis of the data which is obtained from Special School Tegar Harapan, Yogyakarta, then on the second stage refers to analysis discussion towards the results on first stage using Philosophy of Education theory capability approach. The result of this research is that the thematic learning model could become an academic methodology in learning by the students in Special School Tegar Harapan. The thematic learning model also contributes to building basic capability for students in Special School Tegar Harapan, especially on a high education level. The application of model thematic learning for students Special School Tegar Harapan which has various special needs conditions can build basic capability for students according to their interests, potentials, and capabilities. The application of model thematic learning for children with special needs becomes a realization of educational philosophy in the field of special education.